Robots poètes chez Stanisław Lem : réflexions sur la nécessaire étrangeté de la langue littéraire en contexte soviétique - Sylvia Chassaing (ReS Futurae)
By studying the short story « The first sally (A), or Trurl’s electronic bard » and its main character, a poet robot, this article aims at showing what is at stake, both from a literary and a political point of view, in the stylistic choices made by Stanisław Lem in the Cyberiad. Firstly, the archaisms can be construed as references to Swift and Rabelais, which places Lem within a humanist tradition that takes issue in authority. This humanist criticism is here aimed against a narrow understanding of science and logic which was characteristic of the late Soviet period. Simultaneously, the use of both archaisms and neologisms makes this criticism less direct by hiding its topicality, which allows Lem to get around state censorship. The short story is then one example of « Esopic language », whose aim was to deliver hidden messages to the reader via a change in setting or the use of a fable. Finally, stylistic strangeness is therefore also the trace of the constraints under which texts were written in post-war communist Poland, as much as of the strategies that Lem found to circumvent them.